Student Engagement and Disengagement as a Collective Action Problem - Hal A. Lawson; Michael A. Lawson (MDPI AG, 2020)
Isolated teachers in stand-alone American schools are expected to engage diverse students in the quest to facilitate their academic learning and achievement. This strategy assumes that all students will come to school ready and able to learn, and educators in stand-alone schools can meet the needs of all students. Student disengagement gets short shrift in this framework, and so does teacher disengagement. A growing body of research emphasizes needs for nuanced engagement frameworks, better data systems, customized interventions facilitated by intervention registries, and bridge building between schools and community health, mental health, and social service agencies. Here, engagement and disengagement challenges are reframed as opportunities for collective action, including interprofessional teams, community agency-school partnerships, cross-sector collective impact formations, cradle-to-career system building, and community development initiatives. Together these collective action forms signal new institutional designs which are fit for purpose when child/family poverty, social exclusion, and social isolation conspire against student engagement and school success.